Understanding the nonreligious - Henzel, Cynthia Kennedy (Understanding world religions and beliefs., 2019)
Describes the history of nonreligious belief, the battle between governments and religion, the difference between agnostics and atheists, the rising popularity and culture of the nonreligious, and new types of nonreligious groups. Includes a facts section, color photographs, a glossary, and further resources.